Du rôle des affaires dans la politique canadienne d'aide au développement : le cas des télécommunications - Martinez, Andréa (Études internationales, 1994)
This article focuses on the reorientation of the Canadian development assistance policy during the 1980's to foster the emergence of a North-South partnership in which the business community would be a key actor. It is questionable whether the funding levels and geographical priorities of telecommunication projects undertaken by the Canadian private sector through CIDA'S Industrial Cooperation Program may lead to such a partnership. Sectorial allocations, albeit still sparse, reveal a selective marginalization of Third World Economies, as they are concentrated on a few Latin American and Asian middle-income countries.